2019
DOI: 10.1051/mfreview/2019012
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on blasted tool surfaces as a measure for material flow control in sheet-bulk metal forming

Abstract: Highly integrated and closely tolerated functional components can be produced by sheet-bulk metal forming which is the application of bulk forming operations on sheet metal. These processes are characterized by a successive and/or simultaneous occurrence of different load conditions which reduce the geometrical accuracy of the parts. One challenge within sheet-bulk metal forming is the identification of methods to control the material flow to improve the product quality. A suitable approach is the local modifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Opposing the alternative methods for modifying tool surfaces, such as milling or grinding, blasting offers a high degree of geometrical freedom regarding the treated surfaces. Investigations have shown that abrasive blasting in an upsetting process has significant potential for controlling the material flow [29]. In Figure 17, the surfaces used in forming experiments for this study are shown.…”
Section: Tribological Approachmentioning
confidence: 99%
“…Opposing the alternative methods for modifying tool surfaces, such as milling or grinding, blasting offers a high degree of geometrical freedom regarding the treated surfaces. Investigations have shown that abrasive blasting in an upsetting process has significant potential for controlling the material flow [29]. In Figure 17, the surfaces used in forming experiments for this study are shown.…”
Section: Tribological Approachmentioning
confidence: 99%
“…Hereby, the adjustment of the surface roughness plays an important role, as it is directly linked to the resulting friction and the material flow of the process [3]. Through the establishment of a beneficial friction gradient, which means the surface roughening and smoothening in certain tool areas, an improvement of the process result while maintaining acceptable process forces and respectively tool loads can be achieved [4]. To further analyse tailored surfaces, two variants of modifications are investigated within this study.…”
Section: Introductionmentioning
confidence: 99%